The improvement of the color rendering index using convex-dual-layer remote phosphor geometry with YOCl:Eu3+ - Dieu An Nguyen Thi; Binh Le Nguyen Hoa (Universitas Ahmad Dahlan, 2023)
White-light emitting diodes (WLEDs) are semiconductor light sources whose construction design is usually made up of a single pumping chip and a single light-conversion film of phosphor compound. The outstanding problem of this traditional setting is the inadequate chroma rendering index (CRI). Introducing a cluster of multiple blue chips with more than one phosphor layer is demonstrated to address that flaw of W-LEDs. This package is called the dual-film remote-phosphor multi-chip WLED. As a consequence, both the light brightness and the CRI are improved. However, for the maximum results, the test on the second layer of phosphor has been performed to continually alter the proportions and densities of phosphor within the silicone. The researchers employed a unique hue design to control the white-light light emitting diode (LED) module. When comparing the actual result to the simulated color coordinates under the hue standard of international commission on illumination (CIE) 1931, the highest difference is found to be around 0.0063 for correlated color temperatures (CCT) of 6600 K and 7700 K. Experiments indicate that the setting of multi-chip and dual-phosphorus is the optimal design for supporting CRI quality and luminous intensity.